The Social and Ecological Problem of Community Empowerment Base Village Tourism - Murdianto, Murdianto; 'Ainun Zeva Zachari (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Village tourism-based community empowerment in Indonesia has implications for several social issues. This study aims to map an socio-ecological problem and fundamental criticisms of village tourism-based community empowerment programs. Literature research on ten recent research documents using content analysis uncovered several important conclusions: village tourism-based community empowerment has given rise to several anomalies: 1) extreme changes and dependence on tourism sector revenues, 2) land conversion and capitalization, and 3) disparities between village elites and ordinary citizens.